Changes in gastrocnemius MTU stiffness and their correlation with plantar pressure in patients with knee osteoarthritis - Wang, Wenjing; Li, Feng; Guo, Jiayi; Zhang, Zhijie (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Abnormal, excessive, and repetitive knee load is a critical risk factor for osteoarthritis (OA). The gastrocnemius muscle-tendon unit (MTU) interacts with foot biomechanics and is vital in cushioning the knee load. Abnormal gastrocnemius activation and plantar pressure during walking in patients with knee OA may negatively affect gastrocnemius MTU stiffness, increasing knee load. Few studies investigated the relationship between gastrocnemius MTU stiffness and plantar pressure. This study aimed to evaluate the changes in gastrocnemius MTU stiffness in patients with knee OA and their correlations with plantar pressure and clinical symptoms. Methods: Thirty women patients with unilateral knee OA and 30 healthy women participants were recruited. Shear wave elastography was used to quantify gastrocnemius MTU stiffness in ankle resting and anatomical 0° positions, defined as natural and neutral positions in this study. A plantar pressure analysis system was used to collect the plantar pressure parameters on the symptomatic side in patients with knee OA. The Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and Visual Analogue Scale (VAS) scores were used to measure the severity of clinical symptoms. Results: Medial and lateral gastrocnemius (MG and LG) stiffness on both the asymptomatic and symptomatic sides in patients with knee OA was increased compared with that in healthy participants. The MG and LG optimal cutoff stiffness in the natural position was 15.73 kPa and 14.25 kPa, respectively. The optimal cutoff stiffness in the neutral position was 36.32kPa and 25.43kPa, respectively, with excellent sensitivity and specificity. The MG and LG stiffness were positively correlated with the percentages of anterior and medial plantar pressure and negatively correlated with the length of pressure center path. The LG and MG were significantly correlated with WOMAC and VAS scores. Conclusion: Patients with knee OA have increased gastrocnemius muscle stiffness, closely related to plantar pressure and clinical symptoms. Monitoring the gastrocnemius muscle in patients with knee OA can provide an essential basis for its prevention and treatment.